Ear Development of some Local and Australian wheat Varieties in Different Temperature Regimes - Rashid, Ahmad H. A. Hama (Sulaimani Journal for Pure and Applied Sciences, 1999)
The effects of three day/night temperature regimes (15/10, 20/15, and 25/20 for 12/12 hr) on growth and development of ears in eight varieties of two groups of wheat (Local and Australian) Triticum aestivum L. wears studied in laboratory. The results showed that the spikelet number increased slightly by increasing temperature from 15/10 up to 20/15 c. Whereas, further increase in temperature decreased it in most varieties. the rate of spiklelet initiation was also enhanced, but almost the duration of the vegetative and spikelet phases and the apex length at flower initiation reduced in almost all varieties when the temperature was increased to 20/15 c. With further increase in temperature, the rate of spikelet initiation and apex length decreased in all varieties, but the duration of vegetative and spikelet phases either increased or slightly changed. In general, the superiority of Australian varieties was evident. Moreover, the correlation between some plant characters were shown.